2006
DOI: 10.1007/s00441-006-0333-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key tissue type for antler regeneration through pedicle periosteum deletion

Abstract: Epimorphic regeneration is the "holy grail" of regenerative medicine. Research aimed at investigating the various models of epimorphic regeneration is essential if a fundamental understanding of the factors underpinning this process are to be established. Deer antlers are the only mammalian appendages that are subject to an annual cycle of epimorphic regeneration. In our previous studies, we have reported that histogenesis of antler regeneration relies on cells resident within the pedicle periosteum (PP). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 13 publications
2
61
0
2
Order By: Relevance
“…The view that antler regeneration depends on the pedicle periosteum has recently been strongly supported by experimental evidence. Thus, deletion of the periosteum from the pedicle of red deer precluded antler regeneration or delayed this process until after the pedicle periosteum had regenerated (Li et al, 2007a). Gruber (1937), based on a study in roe deer, suggested that cells originating from the marrow spaces of the pedicle bone also contribute to the regenerating antler.…”
Section: Basic Aspects Of Antler Regeneration and Comparison With Limmentioning
confidence: 96%
“…The view that antler regeneration depends on the pedicle periosteum has recently been strongly supported by experimental evidence. Thus, deletion of the periosteum from the pedicle of red deer precluded antler regeneration or delayed this process until after the pedicle periosteum had regenerated (Li et al, 2007a). Gruber (1937), based on a study in roe deer, suggested that cells originating from the marrow spaces of the pedicle bone also contribute to the regenerating antler.…”
Section: Basic Aspects Of Antler Regeneration and Comparison With Limmentioning
confidence: 96%
“…In conclusion, cell dedifferentiation is likely one regeneration strategy in adult S. macrurus, but it is not a requirement in the regeneration of skeletal muscle and the musclederived electric organ. Similarly, the incidence of tissue-specific stem cells contributing to the blastema in adults has been reported in limb regeneration in urodele amphibians (Morrison et al, 2006) and antler regeneration in deer (Li et al, 2007). These reports emphasize the significance of investigating a broad range of species in order to expand our knowledge on the different strategies used to restore lost tissues and assess the extent to which the identified cellular and molecular mechanisms that produce new cells are conserved across different groups.…”
Section: Discussionmentioning
confidence: 72%
“…For example, generation of reliable cell markers have led to recent findings that resident, tissuespecific stem cells also respond to injury and contribute to blastema formation in some vertebrate species (Li et al, 2007;Morrison et al, 2006;Poss et al, 2003;Singh et al, 2012;Weber et al, 2012). Hence, the extent to which cell dedifferentiation versus stem cell activation occurs in response to injury in vertebrates warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that the mesenchymal growth zones of the main beam and the brow tine of red deer form very early during the regeneration process by a local thickening of the PP [42] . That cells of the PP are responsible for antler regeneration has also been supported experimentally [57] . Thus, surgical removal of the PP in red deer stags either inhibited antler regeneration throughout the following antler growth season or delayed the process until after the PP had regenerated.…”
Section: Histo-and Morphogenesis Of the Regenerating Antlermentioning
confidence: 73%
“…Thus, surgical removal of the PP in red deer stags either inhibited antler regeneration throughout the following antler growth season or delayed the process until after the PP had regenerated. Since in this experiment the pedicles had been cut about 1 cm below the antler/ pedicle junction and the cut surface sealed with bone wax, participation of cells derived from the pedicle bone proper (as opposed to the PP) in the regeneration process could be largely excluded [57] .…”
Section: Histo-and Morphogenesis Of the Regenerating Antlermentioning
confidence: 99%